A Physical Bottleneck Increases Predation on Atlantic Salmon Smolts During Seaward Migration in an Irish Index River - Sortland, Lene Klubben; Wightman, Glen; Flávio, Hugo; Aarestrup, Kim; Roche, William (Fisheries management and ecology, 2025)
ABSTRACT Counting departing smolts and returning adults in index rivers is essential to estimate marine survival and track population trends of Atlantic salmon (Salmo salar). However, mortalities between counting facilities and a river mouth can skew survival estimates. We used acoustic and radio telemetry to investigate survival, mortality sources and behaviour of wild salmon smolts in the River Erriff, Ireland's index river, and Killary Fjord. Smolts were tagged with acoustic tags in 2017 (n = 40) and 2018 (n = 35) and radio tags in 2018 (n = 30). Survival was low for acoustic‐tagged smolts in 2017 (26%) and 2018 (47%), mainly due to riverine mortality. Terrestrial or avian predators consumed 65% of acoustic‐tagged smolts in 2017 and 67% of radio‐tagged smolts in 2018. Nocturnal migration and ebb tide transportation likely contributed to high estuary survival. High predation on smolts emphasised the importance of assessing freshwater mortality for effective salmon management.